Analysis science process skills of grade viii students on digestive system material - Tuti Lestari; Velia Oktaviani (Biosfer: Jurnal Pendidikan Biologi, 2023)
Science process skills are the ability to solve problems through scientific research. Science process skills serve as a foundation for other cognitive skills such as logical thinking skills, reasoning and problem solving, making students grow into individuals who are able to access information and understand information, so that students are able to apply the knowledge they acquire in real terms. -world context. For this reason, science process skills are important to be trained in the learning process. The purpose of this study was to analyze the mastery of science process skills for Grade VIII students of SMP Negeri 15 Padang on the digestive system material. This research is a descriptive research with a quantitative approach. The population of this study were all students of class VIII, the sampling technique was carried out by random sampling technique, the number of students who were sampled was 60 students. Data collection techniques were carried out by observation, documentation and written tests. The results showed that the average value of each indicator was divided into three categories, namely high, medium and low. From the results of the study it can be seen that: (1) students get the low category on the indicators of asking questions and formulating hypotheses with a value of 40 and 38.5, (2) students get the medium category on the indicators of investigative skills, classification, interpretation, communication, application. concept, conclude, and predict with a value of 61.2; 69; 52; 52; 60.7; 58.5; and 61.9, (3) students are classified as high on the observation skills indicator with a value of 90 and the average value of mastery of science process skills by students based on the ten indicators used is 58.38, so it can be concluded that mastery of students' science process skills is in medium category.